ARTS EDUCATION IN THE FACE OF CURRENT REGULATIONS (Orfeu, 2020)
The section 36 of the Brazilian Education Law (LDB 9394/96) and its 8th, 9th and 11th paragraphs allowed Brazilian high schools to create formative itineraries aiming artistic education under different curricular arrangements. Those initiatives could allow high school students to follow an artistic career, while fulfilling the mandatory elementary curriculum and studying part of it in diversified part of the curriculum a diverse way, as provided in sections 26 and 35A of the Brazilian Education Law (LDB n. 9394/96). This text is a complement to others published by this author.
Keywords: Brazilian education law; high school; formative itineraries; diversified part of the curriculum; artistic education